2005
DOI: 10.1007/s00449-005-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-limited fed-batch process: an alternative control for Pichia pastoris recombinant protein processes

Abstract: An oxygen-limited fed-batch technique (OLFB) was compared to traditional methanol-limited fed-batch technique (MLFB) for the production of recombinant Thai Rosewood beta-glucosidase with Pichia pastoris. The degree of energy limitation, expressed as the relative rate of respiration (q(O)/q(O,max)), was kept similar in both the types of processes. Due to the higher driving force for oxygen transfer in the OLFB, the oxygen and methanol consumption rates were about 40% higher in the OLFB. The obligate aerobe P. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 25 publications
5
54
1
1
Order By: Relevance
“…The optimum pH value for Pichia growth is approximately 5 (6), but the pH value is commonly reduced to counteract proteolysis (9,32) or to increase both the stability and productivity of heterologous proteins (5,29,56). However, a pH value of 4 or lower can compromise cells during the production process (27).…”
mentioning
confidence: 99%
“…The optimum pH value for Pichia growth is approximately 5 (6), but the pH value is commonly reduced to counteract proteolysis (9,32) or to increase both the stability and productivity of heterologous proteins (5,29,56). However, a pH value of 4 or lower can compromise cells during the production process (27).…”
mentioning
confidence: 99%
“…In the past, in order to avoid oxygen limiting conditions in Pichia cultures, it was common practice for most protocols either to dilute and maintain cell biomass at low levels or to reduce methanol supply [13]. However, two studies have shown that reduced oxygen conditions may be advantageous for the production of recombinant proteins by using P. pastoris AOX1 expression system [17,27]. A model explaining the relationship between specific growth rate and methanol concentration in P. pastoris suggested that the production of hydrogen peroxidase and formaldehyde metabolites is more dependent on methanol concentration than on oxygen intake [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous study of the Mut + phenotype for HBsAg expression was regarded as unfavourable, mainly due to its high demand for oxygen in high density cell cultures that creates oxygen limitation [16]. On the other hand, more recent studies have shown that oxygen limited fed-batch expression may prove advantageous in producing higher cell growth density and obtaining higher product concentration [8,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, the relative respiration rate (RRR) of A. vinelandii diminished drastically; this parameter has been defined as the current respiration rate divided by the maximum respiration rate (Charoenrat et al, 2005). (Díaz-Barrera et al, 2007;Díaz-Barrera et al, 2009) .…”
Section: Vol Um Etri C Oxygen Tr An Sfer Co Effi Ci Ent (Kla) and O Xmentioning
confidence: 99%